Colorado River (Argentina) Water Crisis Scenarios and Influence on Irrigation Water Quality Conditions - Trillini, Mariano; Pierini, Jorge Omar; Vallese, Federico Danilo; Dunel Guerra, Luciana Gisele; Pistonesi, Marcelo Fabian (MDPI, 2023)
The characterization and evaluation of water quality in the Valle Bonaerense del Río Colorado (VBRC), Buenos Aires, Argentina, is necessary, given the immense importance of this region for sustaining the population livelihoods and maintaining the ecological balance, especially in the face of drought and climate change scenarios, and loss of crop production yields. This study evaluated the possible reuse of drainage canals from the perspective of their use for irrigation. Surface water samples were collected at four sampling sites during 2015–2021, one over the Colorado river entering the VBRC, and the remaining three drainage canals flow into the Atlantic Ocean. These physicochemical parameters were performed following the protocols proposed using standard methods: total dissolved solids, pH, electrical conductivity (EC), calcium, magnesium, sodium, potassium, carbonates, bicarbonates, chlorides, sulfates and sodium adsorption ratio were analyzed and classified. The irrigation water quality index (IWQI), principal component analysis, hierarchy of classes analysis and statistical analysis were applied to the dataset. The general hydrochemistry of the VBRC river water indicates a slightly alkaline nature, with a mean pH value of 8.03, and the predominance order of the major ions follows the pattern of Na+ > Ca2+ > Mg2+ > K+, and SO42− > Cl− > HCO3− + CO32− for the anions. For the IWQI, 88.06% of the samples analyzed were classified as safe water for irrigation, and a theoretical yield loss was estimated for crops considering the salinity variable, with vegetables showing the highest losses. The surface water from rivers increases the EC due to the decrease in its discharge because of the water crisis affecting Latin America. Water reuse could be useful for one of the three drainage canals. This study concludes that the reuse of drainage water (S2) has great potential as an adaptation strategy to address the water scarcity and climate change challenges in the Colorado river basin. The research highlights the importance of considering this alternative to achieve sustainable water management in the region. Moreover, the data obtained from the study can be used for making policy and resource management decisions. In view of the possible scenarios of low water flow and increases in the EC values, it is recommended to reorient agricultural production toward crops with higher tolerance to salinity as an alternative, to ensure the sustainability and viability of production in the basin.